Media Pembelajaran Menggunakan Media Canva Terintegrasi IT Untuk Meningkatkan Keterampilan Literasi Digital Guru Sekolah - Zaki, Ahmad; Sappaile, Baso Intang; Talib, Ahmad; Mulbar, Usman; Ahmad, Khawaritzmi Abdallah (Jurnal Hasil-Hasil Pengabdian dan Pemberdayaan Masyarakat, 2025)
The Community Service Program (PKM) was conducted through training, mentoring, and assistance in the development of learning media using Canva, with the aim of enhancing digital literacy skills. The activity was held on Wednesday, July 23, 2025, at SMP Negeri 1 Maros, located in Maros Regency, South Sulawesi Province. The participants of the PKM activity were school teachers from across Maros Regency. The materials presented during the activity included: Concepts and theories of learning media; Types of learning media; Development of learning media using Canva; Implementation of Canva-based learning media in classroom instruction to enhance digital literacy skills. The outcomes achieved from the PKM activity were as follows: Increased competence and knowledge regarding the concepts and theories of IT-based learning media; Improved skills and capabilities in developing learning media using Canva; The ability to implement learning media developed with Canva in classroom teaching; Enhanced digital literacy skills among teachers in developing digital learning media using Canva; Improved IT proficiency and digital literacy skills among students through the use of IT-based learning media in classroom instruction. The outputs of the program included: A report on the implementation of the PKM activity; A scientific article published in a nationally accredited journal with an ISBN; An article published in print or electronic mass media; A video documenting the activity, widely published through online platforms such as YouTube; Improved empowerment of partner schools in line with the identified challenges and needs.